2012
DOI: 10.2176/nmc.52.829
|View full text |Cite
|
Sign up to set email alerts
|

Combined Endovascular and Endoscopic Surgery for Acute Epidural Hematoma in a Patient With Poor Health

Abstract: A 74-year-old woman presented with right acute epidural hematoma (AEDH) associated with a skull fracture after a fall. Emergency craniotomy under general anesthesia could not be performed because of her poor medical condition. Therefore, transfemoral endovascular embolization and hematoma evacuation via a burr hole were performed using endoscopy under local anesthesia. The patient recovered and was discharged without neurological deficits. AEDH is a common traumatic disease often requiring emergency craniotomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The patient originally had an SDH and developed an EDH (which was drained in a second operation) but rebled and was finally treated successfully with embolization. Ohshima et al 20 described the combined treatment of a large EDH with bur hole endoscopic evacuation and MMA embolization in a 74-year-old patient in poor medical condition. Kim et al 13 described the usefulness of intraoperative embolization of an MMA pseudoaneurysm for hemostasis as a desperate measure to control acute, life-threatening, uncontrollable bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient originally had an SDH and developed an EDH (which was drained in a second operation) but rebled and was finally treated successfully with embolization. Ohshima et al 20 described the combined treatment of a large EDH with bur hole endoscopic evacuation and MMA embolization in a 74-year-old patient in poor medical condition. Kim et al 13 described the usefulness of intraoperative embolization of an MMA pseudoaneurysm for hemostasis as a desperate measure to control acute, life-threatening, uncontrollable bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…vascular lesions associated with small EDHs has been proposed as a safe and effective treatment option. 6,20,24,28 In this paper, we describe our experience with the endovascular management of EDHs in 80 consecutive patients (thus far the largest reported series to the best of our knowledge), and compare it with historical cohorts.…”
mentioning
confidence: 99%
“…Endovascular treatment, commonly used for various conditions, has been applied in trauma patients for issues like traumatic carotid cavernous fistulas, pseudoaneurysms, and intractable bleeding. Reports exist of endovascular embolization for small acute epidural hematomas, demonstrating no postoperative complications [ [11] , [12] , [13] , [14] ]. In a previously reported case, we performed MMA embolization for a small acute epidural hematoma in a 65-year-old man who had sustained an injury from a fall.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature, including the present case, revealed 15 articles of embolization for EDH in 153 patients [ Table 1 ]. [ 3 , 5 , 8 , 19 , 21 , 22 , 24 , 27 , 29 , 32 , 36 , 39 , 41 , 42 ] In 98.0% of cases (150/153), EDH occurred due to traumatic injury; 1 case (0.69%) was caused by a nontraumatic dural arteriovenous fistula. [ 39 ] The MMA was embolized in all cases (100%), leading to successful outcome with no complications in all but 1 complicated case, where the patient died of hypoxic injury and medical conditions 2 months after treatment for intracranial hemorrhage requiring an external ventricular drain.…”
Section: Discussionmentioning
confidence: 99%